Hand-operated and rotary mity instruments in combination with an endodontic handpiece and endodontic motor preparation: A comparison of shaping ability in simulated curved root canals - Maria Giraki; Edith Harapetian; Stefan Rüttermann; Susanne Gerhardt-Szep (Journal of Dental Problems and Solutions - Peertechz Publications, 2019)
The aim of this in vitro pilot study was to describe the shaping ability of a rotary nickel-titanium (NiTi) instrument in combination with different torque-controlled endodontic devices and to compare them with NiTi files in combination with a conventional preparation by hand in severely curved root canals of plastic blocks. Thirty blocks simulating a severely curved root canal were divided into three groups (n=10 for each). All canals were prepared with NiTi files to an ISO size of 40 using an apical-coronal preparation technique. Mity Roto 360° files (Loser, Leverkusen, Germany) were used for the automatic systems, while Mity K-Files (Loser, Leverkusen, Germany) were used for the preparation by hand. We evaluated the frequency of instrument failure, the preparation time, loss of working length, loss of weight, elbow-zip effects, and changes in root canal anatomy. The data were analyzed statistically using one-way ANOVA followed by a post hoc Bonferroni test (p < 0.05). A total of three instrument failures were observed: one for Mtwo direct and two for Endo IT. Preparation time was significantly longer when preparing by hand (16.64 min) than for both automatic systems, which did not differ significantly. Critical loss of working length could be detected for all systems (1.3-2.81 mm). Irrespective of the torque-controlled motor, the shape of the canal anatomy was retained better with Mity Roto files than hand preparation. In summary, the two automatic systems did not differ significantly. Within the limitations of this study and especially due to the long working length losses, neither the MTwo direct handpiece nor the Endo IT professional motor can be recommended in combination with Mity Roto 360° files when an apical-coronal preparation method is used in severely curved root canals.